Islamic insurance (Takaful): determinant acceptance of people in Melaka / An’nur Sharieda Nadzri - Nadzri, An’nur Sharieda (Faculty of Business and Management, 2011)
This study is obtaining to determine the acceptance of Islamic insurance (Takaful) in Melaka. Feedback from public on their acceptance of Islamic insurance (Takaful) will be use as a result for the study. The growth of Islamic insurance (Takaful) companies has become a threat for the conventional insurance companies. The impressive growth world wide and potential expansion into new western markets has a strong implication to Takaful operators to gear themselves with innovative Takaful products and to match the service quality of the traditional insurance market to close to a billion Muslim markets scattered in many parts of the world (Zuriah, 2009). Ikhlas Consultant & Services Sdn Bhd Company will be other reference for this study to determine the customers’ acceptance.